Introducing key microbes from high productive soil transforms native soil microbial community of low productive soil. Issue 10 (28th June 2019) - Kandasamy, Saveetha; Liu, Elaine Yi Ran; Patterson, Greg; Saldias, Soledad; Ali, Shimaila; Lazarovits, George
Abstract: This study aimed to understand the changes in rhizosphere microbial structure and diversity of an average corn yielding field site soil with the introduced microbial candidates from a high‐yielding site. Soils used in this study were from two growers' fields located in Dunnville, Ontario, Canada, where one of the farms has an exceptional high corn yield (G‐site soil;ca 20 tons/acre) and the other yields an average crop (H‐site soil; 12 tons/acre) (8 years of unpublished A & L data). In growth room experiments using wheat as the indicator crop, calcium alginate beads with microbes composed of Azospirillum lipoferum, Rhizobium leguminosarum, Burkholderia ambifaria, Burkholderia graminis, Burkholderia vietnamiensis, Pseudomonas lurida, Exiguobacterium acetylicum, Kosakonia cowanii, and Paenibacillus polymyxa was introduced into the soil at planting to the average‐yielding soil. These bacteria had been isolated from the high‐yielding farm soil. Among the nine microbial candidates tested, three ( P. polymyxa, E. acetylicum and K. cowanii ) significantly impacted the plant health and biometrics in addition to microbial richness and diversity, where the microbial profile became very similar to the high productive G‐site soil. One hundred and forty‐two bacterial terminal restriction fragments (TRFs) were involved in the community shift and 48 of them showed significant correlation to several interacting soil factors. This study indicates the potential of shifting microbial profiles of average‐yielding soils by introducing key candidates from highly productive soils to increase biological soil health. Abstract : The key microbes from high yielding sites have the potential on impacting other native microbial communities in the soil. This study aimed to understand the changes in rhizosphere microbial structure and diversity of native average yielding field site soil with the introduced microbial candidates from high yielding farms under greenhouse conditions. Outcome of the study indicated the potential to shift the microbial profile of average yielding sites by specifically introducing the potential key candidate from the high yielding sites to obtain sustainable biological soil health. To our knowledge, this is the first study describes the significance of the use of key individual microbes for community shift to transform low productive soils.